Brentuximab vedotin in the treatment of paediatric patients with relapsed or refractory Hodgkin's lymphoma: Results of a real‐life study. Issue 10 (2nd June 2022) - Massano, Davide; Carraro, Elisa; Mussolin, Lara; Buffardi, Salvatore; Barat, Veronica; Zama, Daniele; Muggeo, Paola; Vendemini, Francesca; Sau, Antonella; Moleti, Maria Luisa; Verzegnassi, Federico; D'Amico, Salvatore; et al.
Abstract: Background: Brentuximab vedotin (BV) is an antibody drug‐conjugated anti‐CD30 approved for the treatment of adult classical Hodgkin's lymphoma (HL), whereas it is considered as off‐label indication in paediatrics. The aim of the study was to evaluate the safety and efficacy of BV to treat patients aged less than 18 years with refractory/relapsed HL. Materials and methods: In this multicentre, retrospective study, 68 paediatric patients who received at least one dose of BV between November 2011 and August 2020 were enrolled. A median of nine doses of BV were administered as monotherapy ( n = 31) or combined with other therapies ( n = 37). BV was administrated alone as consolidation therapy after stem cell transplantation (SCT) in 12 patients, before SCT in 18 patients, whereas in 15 patients it was used before and after SCT as consolidation therapy. Median follow‐up was 2.8 years (range: 0.6–8.9 years). Results: The best response was observed in the 86% of patients; the overall response rate was 66%. The 3‐year progression‐free survival was 58%, whereas the overall survival was 75%. No statistically significant differences between patients treated with BV monotherapy or combination were highlighted. In multivariate analysis, patients with non‐nodular sclerosis HL and not transplanted had an increased risk of failure. Overall, 46% of patients had grade 3–4 adverse events that led to BV discontinuation in five of them. Conclusion: In conclusion, our study confirms that BV was a safe and effective drug, able to induce complete remission, either as monotherapy or in association with standard therapy.